SINTESIS HUMAN MILK FAT ANALOG KAYA LAURAT MELALUI INTERESTERIFIKASI ENZIMATIS DENGAN BAHAN BAKU VIRGIN COCONUT OIL DAN STEARIN SAWIT - , Steivie Karouw, STP, M.Sc, Dr.Ir. Suparmo, MSc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main objective of this study was to synthesize HMF analog having high percentage of palmitic acid in the sn-2 and high lauric acid in the sn-1,3 positions. More special the objectives of this study were 1) to obtain preparation method of high lauric fatty acid methyl ester from coconut oil through chemical methanolysis and dry fractionation, as raw materials for synthesis of HMF analog, 2) to determine the enzyme and the enzymatic hydrolysis condition to obtain high palmitate 2-monoglyceride from palm stearin, 3) to determine enzymatic esterification condition for producing HMF analog, and 4) to determine oxidation and hydrolysis stability of the resulted HMF analog. This research was conducted in 4 steps as follows: The first step was synthesis and fractionation of high lauric fatty acid methyl ester from VCO